Caracterização do composto luminescente CdSiO3 produzido por rota de sol-gel - Abreu, Carolina Melo de (2015)
Cadmium silicate in composition CdSiO3 is a phosphorescent material with potential applications in areas such as emergency lights, opto-electronic devices and coating of ceramic tiles for use in radiodiagnostic rooms. The main goal of the present work was to investigate the sol-gel synthesis and optical properties of cadmium silicate (CdSiO3) undoped and doped with the transition metals (Mn, Ni, Fe and Co) and rare earths (Gd and Tb). Physical parameters such as starting pH, deviation from stoichiometry, calcination time and temperature were analyzed to obtain the best conditions for sample preparation. The single crystalline phase CdSiO3 was obtained at pH 7.0 (700 ° C/3h) and pH 1.0 (1000 ° C/3h). The optical properties of the synthesized powders were studied by a combination of Optical Absorption (OA), Photoluminescence (PL), X-ray Excited Optical Luminescence (XEOL), Thermoluminescence (TL) and lifetime measurements. According to the results obtained using OA, the optical band gap of the CdSiO3 was estimated at around 5 eV, while the self-trapped exciton level (STE) was obtained at about 4.7 eV. The absorption in the visible range (570 and 800 nm) may be due to intrinsic defects (color center) as cadmium and oxygen vacancies present in the CdSiO3. The PL and XEOL emission spectra of the undoped sample presented broad emission bands at 400, 490 and 590 nm with different relative intensities that depend on the pH, temperature and deviation from stoichiometry causing color changes in the emission of CdSiO3. The three luminescent channels can be related to: (i) direct recombination of electrons from the conduction band with holes from the valence band; (ii) recombination of excitons and (iii) emission from color centers possibly related to impurities, intrinsic defects and dopants present at low concentration. In this work, the mapping of the luminescence shows that the intrinsic luminescence of CdSiO3 can be influenced by production method. The presence of dopants (Mn, Gd and Tb) increased the luminescence intensity and the afterglow of CdSiO3. However, the dopants (Ni, Co and Fe) suppressed the luminescence due to self-absorption processes. This work enabled the development of phosphors CdSiO3 with violet, blue, green, yellow, orange, pink and white emission.